Functionalized Hydrogels for Articular Cartilage Tissue Engineering. (June 2022) - Zhou, Liangbin; Guo, Peng; D'Este, Matteo; Tong, Wenxue; Xu, Jiankun; Yao, Hao; Stoddart, Martin J.; van Osch, Gerjo J.V.M.; Ho, Kevin Ki-Wai; Li, Zhen; Qin, Ling
Abstract: Articular cartilage (AC) is an avascular and flexible connective tissue located on the bone surface in the diarthrodial joints. AC defects are common in the knees of young and physically active individuals. Because of the lack of suitable tissue-engineered artificial matrices, current therapies for AC defects, especially full-thickness AC defects and osteochondral interfaces, fail to replace or regenerate damaged cartilage adequately. With rapid research and development advancements in AC tissue engineering (ACTE), functionalized hydrogels have emerged as promising cartilage matrix substitutes because of their favorable biomechanical properties, water content, swelling ability, cytocompatibility, biodegradability, and lubricating behaviors. They can be rationally designed and conveniently tuned to simulate the extracellular matrix of cartilage. This article briefly introduces the composition, structure, and function of AC and its defects, followed by a comprehensive review of the exquisite (bio)design and (bio)fabrication of functionalized hydrogels for AC repair. Finally, we summarize the challenges encountered in functionalized hydrogel-based strategies for ACTE both in vivo and in vitro and the future directions for clinical translation.